Performance bonds and injunction : an unconscionable conduct / Nur 'Ain Ismail , Norazlin Mat Salleh and Nor Nazihah Chuweni - Ismail, Nur 'Ain; Mat Salleh, Norazlin; Chuweni, Nor Nazihah (2012)
Performance bonds and guarantees have been the subject of considerable litigation either in Malaysia or other law jurisdiction. Performance bond and guarantees given are considered as a security to the beneficiary but there are triggering events which restrain a call or payment of the bond. Injunction will be granted if there are serious issues to be tried; fraudulent and unconscionable conduct by parties in trial; balance of convenience; and irretrievable damages. In the English courts, an injunction for restraining a call or payment upon the bond will be granted if there is an existence of fraud or unconscionable conduct. However, this research aims to identify either the English judgment is applied in Malaysian courts. Hence, the objective of this study is to determine the legal interpretation on the application of injunction to restrain a call of the bond and payment received in performance bond particularly on unconscionable conduct. In order to achieve the objective, the research is conducted through legal analysis of reported and unreported court decisions in Malaysia and South East Asian countries. From the analysis, the differences of circumstances of unconscionably conducts are identified as well as the reasons for not granting the injunction relief or any principles to be applied in the cases in order to prevent the banks from making payment and dealing with the calling of the bond.